THE LINGUISTIC AND CULTURAL SIGNIFICANCE OF EPONYMS IN ENGLISH (Web of Teachers: Inderscience Research, 2026)
The linguistic and cultural role of eponyms in the modern English language is examined in this paper. Obviously, eponyms constitute a significant and productive layer of vocabulary formed from proper names of historical figures, literary characters, scientists, geographical places, and mythological characters. Over time, many eponyms turn into common lexical units, acquiring new semantic, stylistic, and connotative meanings. Thus, the study aims to analyze the functional role of eponyms in the English lexical system and to identify their linguo-cultural characteristics in modern discourse. Descriptive, semantic, contextual, and linguo-cultural methods of analysis is applied in the research. Special attention is given to the processes of semantic transformation, metaphorization, and lexicalization of eponymic units. The study also investigates the nominative, expressive, evaluative, and stylistic functions of eponyms in different communicative contexts. The findings demonstrate that eponyms serve not only as linguistic units for naming objects and phenomena but also as carriers of cultural memory, historical knowledge, and collective social experience. Many English eponyms reflect national traditions, historical events, literary heritage, and cultural stereotypes, thereby contributing to the interaction between language and culture. Furthermore, modern media and digital communication actively promote the emergence and dissemination of new eponymic expressions. The study concludes that eponyms hold a significant place in the English lexical system due to their multifunctional character and high communicative potential. They enrich vocabulary, enhance expressiveness, and preserve cultural information within language. The research may contribute to further studies in lexicology, linguo-culturology, cognitive linguistics, and translation studies.